PENGARUH FAKTOR MOTIVASI TERIIADAP ORIENTASI KEWIRAUSAHAAN DAN KEPUASAN PADA WIRAUSAHA BATIK DI PEKALONGAN - , Zahrozatul Firdausa ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Micro, small and medium enterprises have an important role in the growth of a country. Batik business dominate industrial activity in Pekalongan and most able to absorb labor. The purpose of this research is to study the motivational factors that influence entrepreneurial orientation and their satisfaction. This study explores the variables that influence and impact on the entrepreneurial orientation and satisfication. The method used was to distribute questionnaires to 100 respondents. Data analysis was performed using Structural Equation Modeling (SEM) with a program SmartPLS (Partial Least Square) 2.0. The results showed that the pull motivational factors play an important role as an excuse for entrepreneurs to enter this field. These pull motivational factors are shown to affect and influence the level of entrepreneurial orientation on entrepreneurial satisfaction. Instead push motivational factors were not proven able to influence entrepreneurial orientation and entrepreneurial satisfaction. This study shows that Pekalongan batik entrepreneurs are willing to take risks, be proactive and innovative, and derive satisfaction in the operations.